2010
DOI: 10.1038/ncomms1036
|View full text |Cite
|
Sign up to set email alerts
|

Divergent transcriptional activities determine limb identity

Abstract: Limbs develop using a common genetic programme despite widely differing morphologies. This programme is modulated by limb-restricted regulators such as hindlimb (HL) transcription factors Pitx1 and Tbx4 and the forelimb (FL) Tbx5. Both Tbx factors have been implicated in limb patterning and growth, but their relative activities and underlying mechanisms remain unclear. In this paper, we show that Tbx4 and Tbx5 harbour conserved and divergent transcriptional regulatory do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 42 publications
0
50
1
Order By: Relevance
“…Together, these data demonstrate that Pitx1 determines hindlimb morphology independently of Tbx4. Our results differ from those recently published by Ouimette and colleagues (Ouimette et al, 2010) who have proposed that a unique Tbx4 repressor activity is the primary effector of hindlimb identity. This study used a similar transgene gene replacement strategy in the background of a Pitx1 mutant.…”
Section: Pitx1 Shapes Hindlimb Morphologies Independently Of Tbx4 Actcontrasting
confidence: 99%
“…Together, these data demonstrate that Pitx1 determines hindlimb morphology independently of Tbx4. Our results differ from those recently published by Ouimette and colleagues (Ouimette et al, 2010) who have proposed that a unique Tbx4 repressor activity is the primary effector of hindlimb identity. This study used a similar transgene gene replacement strategy in the background of a Pitx1 mutant.…”
Section: Pitx1 Shapes Hindlimb Morphologies Independently Of Tbx4 Actcontrasting
confidence: 99%
“…Therefore, we examined the expression of the hindlimb fieldspecific genes Pitx1 and Tbx4 in order to assess a possible role of Islet1 in the specification of limb identity. Genetic analysis has suggested that Tbx4 expression is driven by the hindlimb-specific program, although its role in hindlimb specificity remains controversial (Minguillon et al, 2005;Naiche and Papaioannou, 2007;Ouimette et al, 2010). We observed a slightly weaker signal for Pitx1 expression and significant downregulation of Tbx4 in the LPM (Fig.…”
Section: Islet1 Regulates Expression Of Tbx4 But Not Pitx1 In the Lpmmentioning
confidence: 71%
“…Islet1 appears to not be required for establishing hindlimb bud-specific characters Pitx1, a homeodomain protein, is required and sufficient for determining hindlimb-specific characters (DeLaurier et al, 2006;Lanctot et al, 1999;Logan and Tabin, 1999;Szeto et al, 1999), whereas the role of Tbx4, a T-box transcription factor, in hindlimb specification remains controversial (Minguillon et al, 2005;Naiche and Papaioannou, 2007;Ouimette et al, 2010). Localized expression of Islet1 in hindlimb progenitors (Yang et al, 2006) suggests that it might be involved in establishing hindlimb-specific characters.…”
Section: Research Articlementioning
confidence: 99%